Reflections on inclusive leadership education: from professional communities of practices to students - Francesco Maiorana; Lidia Nazzaro; Alice Severi; Angela Ciolli; Marina Porta; Giusy Cristaldi; Mirko Labbri (IUL Research, 2022)
The central role of education has been part of discourse since ancient times. We will investigate the role of leadership in education from Communities of Practice (CoP) to students, the leaders of tomorrow. This will be done through the direct experience of the authors related to their enacted educational activity, experiences described through the lens of leadership and its development process in class, school, and in local and national communities. Reflections and best practices will conclude the work.